The Big, the Bad and the Average: Hedonic Prices and Inverse Demand for Baltic Cod - Cecilia Hammarlund (Lund University, School of Economics and Management, Department of Economics, 2013)
The price of fish depends on quality attributes such as size and freshness. In turn, quality attributes are related to fishery management. This article presents a hedonic analysis where attribute prices of size and quality ratings are estimated for the Swedish Baltic Cod Fishery. Using information from 5307 landing days, hedonic inverse demand functions are estimated with a random coefficient model. Results show that there are price premiums for larger sizes of cod and for cod with the highest quality rating. Results also show that own- quantity effects and cross-quantity effects are negative for most attributes. Thus, there is indication that the quality composition of landed fish affect the prices of quality attributes and that the management of a fish stock that changes the quantity of attributes will also change the prices of fish.
Keywords: D21; Q22; 330; Attribute prices; Hedonic inverse demand; Baltic Cod fishery